The compensation mechanism in the RAINS model: The Norwegian targets for acidification - Finn R. Førsund; Ove Wolfgang (University of Oslo, Department of Economics, 2001)
The RAINS model is used to calculate cost minimising abatement policies subject to European-wide spatial restrictions on pollution. The principle for choosing environmental targets for the 1994 Oslo Protocol was closing a gap between benchmark- and critical loads for each grid with a uniform percentage. During the negotiations for the 1999 Gothenburg Protocol accumulated ecosystems exceedances was adapted as basis for gap closure, and overshooting of the constraints allowed as an option, provided compensation could be found within the same country. A theoretical discussion of this compensation mechanism is provided. A simulation study, using the full RAINS model, of the impact of different levels of targets for troublesome Norwegian grids is presented, and results in the form of changes in accumulated acidity excesses and costs for the participating countries are reported.
Keywords: C44; C61; Q25; 330; Acid rain; RAINS; critical loads; gap closure; accumulated exceedances; compensation mechanism; Saurer Regen; Luftreinhaltung; Wirtschaftsmodell; Norwegen